Educational Status Number of Previous Contraceptive Failure Do not Effect the Women’s Contraceptive Preference After Surgical Abortion in Turkey - Özkaya, Enis; Korkmaz, Vakkas; Kara, Osman Fadıl; Küçüközkan, Tuncay (Gynecology Obstetrics & Reproductive Medicine, 2010)
OBJECTIVE: The aim of this study was to investigate the determinants of the contraceptive preference of couples after surgical abortion result of contraceptive failure or no contraception. STUDY DESIGN: Study population consisted of 302 women who admitted to Dr. Sami Ulus Maternity and Women’s Health Teaching and Research Hospital family planning unit and underwent surgical abortion. All pregnancies were in their 5-10 th weeks of gestation. Gravida, parity, number of previous surgical abortions, living children number, last pregnancy status with current contraceptive method were recorded. RESULTS: Mean age, gravida, parity, number of previous surgical abortions and living children were 31.05±6.52 (19-46 years), 4.30±1.83 (1-11), 2.33±1.32 (0-7), 0.96±1.05 (0-5), 2.28±1.29 (0-7) respectively. There were 183 (60,6%) women with previous surgical abortions, mean number of surgical abortions were 1.59±0.6. Among these patients there were 82 (45%) patients using no contraceptive method and 55 (30%) women were using coitus interruptus. Condoms were being used only by 29 (16%) women. Oral contraceptives (OCS) were being used in 11 (6%) women. No association was observed between condom or OCS use and educational status (p=0.786) in these patients. Condom or OCS users a little bit younger but not reached statistical significance (p=0.071). Women with different contraceptive use were similar in terms of gravida, parity, interval from previous pregnancy (p=0.423, p=0.402, 0.467 respectively). No association was obtained between number of previous surgical abortion, current contraceptive use (p=0.386) and educational status (p=0.735). CONCLUSION: Our study suggests that educational status, number previous contraceptive failure or maternal age does not effect the contraceptive preference after surgical abortion.